Improving Employee Performance through Compensation at the Central Java Education and Culture Office with Motivation as an Intervening Variable - Djati, Ardiptha Dharma; Sari, Raden Ayu Aminah Rizkia Puspita; Amron; Perdana, Tito Aditya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Compensation is an important element in an organization that affects the performance and sustainability of human resources. This study aims to analyze the relationship between compensation, motivation, and employee performance with motivation as a mediating variable in the Central Java Education and Culture Office. The study used a quantitative approach with a sample of 100 respondents analyzed using SPSS Statistics 25. The results of the study explain that compensation does not directly affect employee performance but has a significant effect on motivation. Motivation has been shown to have a significant effect on performance and acts as a mediator between compensation and employee performance. The theoretical implication of this study is to enrich the literature on the role of motivation as a mediating variable in the relationship between compensation and employee performance, especially in the context of government agencies. Practically, these results provide insight for human resource managers to focus more on compensation distribution strategies that can improve performance, so that they have a significant effect on employee performance. Proper implementation will help improve performance and achieve institutional goals.